2021
DOI: 10.1007/s00044-021-02750-5
|View full text |Cite
|
Sign up to set email alerts
|

Thiouracil SecA inhibitors: bypassing the effects of efflux pumps and attenuating virulence factor secretion in MRSA and Bacillus anthracis

Abstract: We have previously reported a series of thiouracil analogs as bacterial SecA inhibitors. In this study, one potent thiouracil analog, SCA-15, was further evaluated for its inhibitory effects on SecA proteins and against strains of methicillin-resistant Staphylococcus aureus (MRSA) and Bacillus anthracis Sterne. SCA-15 inhibited the ion-channel activities of SecA1 with IC 50 of 2.0-2.8 μM and the ATPase activities of SecA2 with IC 50 of 13-20 μM, respectively. Drug affinity responsive target stability (DARTS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Additionally, it was recently shown that the SecA2 pathway activates the ATK kinase checkpoint protein, resulting in the formation of double-strand breaks (DBSs) in host DNA [ 64 ]. Several compounds have been identified as potential inhibitors of Sec pathways, including analogs of the dye rose Bengal, thiouracil analogs and thiazolidine derivatives [ 65 , 66 , 67 ].…”
Section: Targeting the Secretory Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was recently shown that the SecA2 pathway activates the ATK kinase checkpoint protein, resulting in the formation of double-strand breaks (DBSs) in host DNA [ 64 ]. Several compounds have been identified as potential inhibitors of Sec pathways, including analogs of the dye rose Bengal, thiouracil analogs and thiazolidine derivatives [ 65 , 66 , 67 ].…”
Section: Targeting the Secretory Systemsmentioning
confidence: 99%
“…Efflux pumps play a crucial role in multi-drug resistance (MDR), often leading to suboptimal drug uptake. Interestingly, these compounds could also be interesting in overcoming the effect of efflux pumps that are responsible for MDR [66]. 5) were tested for anti-mycobacterial activity.…”
Section: Sec Export Pathwaymentioning
confidence: 99%